Oleandrin: A bioactive phytochemical and potential cancer killer via multiple cellular signaling pathways. (September 2020) - Kanwal, Nazia; Rasul, Azhar; Hussain, Ghulam; Anwar, Haseeb; Shah, Muhammad Ajmal; Sarfraz, Iqra; Riaz, Ammara; Batool, Rabia; Shahbaz, Muhammad; Hussain, Arif; Selamoglu, Zeliha
Abstract: Nerium oleander, a member of family Apocynaceae, is commonly known as Kaner in various countries of Asia and Mediterranean region. This plant has been renowned to possess significant therapeutic potential due to its various bioactive compounds which have been isolated from this plant e.g., cardiac glycosides, oleandrin, α-tocopherol, digitoxingenin, urosolic acid, quercetin, odorosides, and adigoside. Oleandrin, a saponin glycoside is one of the most potent and pharmacologically active phytochemicals of N. oleander . Its remarkable pharmacotherapeutic potential have been interpreted as anticancer, anti-inflammatory, anti-HIV, neuroprotective, antimicrobial and antioxidant. This particular bioactive entity is known to target the multiple deregulated signaling cascades of cancer such as NF-κB, MAPK, and PI3K/Akt. The main focus of the current study is to comprehend the action mechanisms of oleandrin against various pathological conditions. The current review is a comprehensive summary to facilitate the researchers to understand the pharmacological position of the oleandrin in the arena of drug discovery, representing this compound as a new drug candidate for further researches. Moreover, in vivo and in silico based studies are required to explore the mechanistic approaches regarding the pharmacokinetics and biosafety profiling of this compound to completely track its candidature status in natural drug discovery. Graphical abstract: Image 1